Virtual reality games for spatial hearing training in children and young people with bilateral cochlear implants: the “Both Ears (BEARS)” approach - Bhavisha J. Parmar; Bhavisha J. Parmar; Marina Salorio-Corbetto; Lorenzo Picinali; Merle Mahon; Ruth Nightingale; Sarah Somerset; Sarah Somerset; Helen Cullington; Sandra Driver; Christine Rocca; Dan Jiang; et al. (Frontiers in Neuroscience)
Spatial hearing relies on the encoding of perceptual sound location cues in space. It is critical for communicating in background noise, and understanding where sounds are coming from (sound localization). Although there are some monoaural spatial hearing cues (i.e., from one ear), most of our spatial hearing skills require binaural hearing (i.e., from two ears). Cochlear implants (CIs) are often the most appropriate rehabilitation for individuals with severe-to-profound hearing loss, with those aged 18 years of age and younger typically receiving bilateral implants (one in each ear). As experience with bilateral hearing increases, individuals tend to improve their spatial hearing skills. Extensive research demonstrates that training can enhance sound localization, speech understanding in noise, and music perception. The BEARS (Both Ears) approach utilizes Virtual Reality (VR) games specifically designed for young people with bilateral CIs to train and improve spatial hearing skills. This paper outlines the BEARS approach by: (i) emphasizing the need for more robust and engaging rehabilitation techniques, (ii) presenting the BEARS logic model that underpins the intervention, and (iii) detailing the assessment tools that will be employed in a clinical trial to evaluate the effectiveness of BEARS in alignment with the logic model.